2015
DOI: 10.1186/s13287-015-0231-x
|View full text |Cite
|
Sign up to set email alerts
|

Human adult stem cells derived from adipose tissue and bone marrow attenuate enteric neuropathy in the guinea-pig model of acute colitis

Abstract: IntroductionMesenchymal stem cells (MSCs) have been identified as a viable treatment for inflammatory bowel disease (IBD). MSCs derived from bone marrow (BM-MSCs) have predominated in experimental models whereas the majority of clinical trials have used MSCs derived from adipose tissue (AT-MSCs), thus there is little consensus on the optimal tissue source. The therapeutic efficacies of these MSCs are yet to be compared in context of the underlying dysfunction of the enteric nervous system innervating the gastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 101 publications
1
31
0
Order By: Relevance
“…To further corroborate the finding that USP7 is an essential player in osteogenic differentiation, we examined the effects of USP7 on the osteogenic commitment of another type of mesenchymal stem cell, human bone marrow-derived mesenchymal stem cells (hBMMSCs) [ 31 ]. Knockdown of USP7 significantly reduced the osteogenic differentiation manifested by both ALP and Alizarin red S staining and quantification (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To further corroborate the finding that USP7 is an essential player in osteogenic differentiation, we examined the effects of USP7 on the osteogenic commitment of another type of mesenchymal stem cell, human bone marrow-derived mesenchymal stem cells (hBMMSCs) [ 31 ]. Knockdown of USP7 significantly reduced the osteogenic differentiation manifested by both ALP and Alizarin red S staining and quantification (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, MSCs have been associated with increased nitric oxide (NO) in a model of Alzheimer's disease which may have been driven by preventing the loss of neuronal nitric oxide synthase (nNOS) 43 . Alternatively, several studies observed a reduction in inflammation‐induced iNOS and nNOS expression after MSC treatment 37,44‐47 . Overall, while the majority of studies support antioxidative effects of MSCs, their antinitrosative effects are unclear and likely to be disease and tissue specific.…”
Section: Effect Of Mscs On Oxidative Stress Biomarkers and Rosmentioning
confidence: 99%
“…In these studies, it was concluded that locally applied bone marrow (BM)-MSCs administered at a dose of 1 × 10 6 are neuroprotective towards enteric neurons compromised by 2,4,6-trinitrobenzene-sulfonate (TNBS)-induced inflammation [25, 35, 57]. These results provide the foundation for examining the neuroprotective potential of MSC therapy in intestinal inflammation.…”
Section: Introductionmentioning
confidence: 99%